Molybdenum disulfide nanoparticles decorated reduced graphene oxide: highly sensitive and selective hydrogen sensor. (14th August 2017) - Venkatesan, A; Rathi, Servin; Lee, In-yeal; Park, Jinwoo; Lim, Dongsuk; Kang, Moonshik; Joh, Han-Ik; Kim, Gil-Ho; Kannan, E S
Abstract: In this work, we report on the hydrogen (H2 ) sensing behavior of reduced graphene oxide (RGO)/molybdenum disulfide (MoS2 ) nano particles (NPs) based composite film. The RGO/MoS2 composite exhibited a highly enhanced H2 response (∼15.6%) for 200 ppm at an operating temperature of 60 °C. Furthermore, the RGO/MoS2 composite showed excellent selectivity to H2 with respect to ammonia (NH3 ) and nitric oxide (NO) which are highly reactive gas species. The composite's response to H2 is 2.9 times higher than that of NH3 whereas for NO it is 3.5. This highly improved H2 sensing response and selectivity of RGO/MoS2 at low operating temperatures were attributed to the structural integration of MoS2 nanoparticles in the nanochannels and pores in the RGO layer.